The lexical boost effect is stronger in main clauses than in subordinate clauses - Rianne van Lieburg; Sarah Bernolet (Frontiers in Language Sciences)
Structural priming effects are stronger if there is lexical overlap between prime and target, the so-called lexical boost effect to structural priming. While abstract structural priming is long-lasting and seems to reflect implicit learning, the lexical boost effect decays quickly and might be induced by residual activation or explicit memory. A recent study only found a lexical boost effect in ditransitive structures in subordinate clauses when the head verb in the subordinate clause rather than the matrix head verb was repeated between prime and target. We report an experiment in which the lexical boost effect is weaker in subordinate clauses than in main clauses when repeating the head verb. Our findings suggest that the lexical boost effect caused by repeating head verbs can be disrupted due to an increased amount of interfering material.